Women at the forefront: raising awareness of climate-resilient varieties to transform the informal seed trade in Tanzania - Mwakatwila, Atupokile; Ochieng, Justus; Cheyo, Esther; Kimisha, Joseph; Mchau, Devotha; Ndunguru, Agness; Kadege, Edith; Bujiku, Anthony; Kabyemela, Anatolius; Mbapila, Shadrack; Mbiu, Julius; Radegunda, Kessy; et al. (Frontiers Media, 2025)
Access to and utilization of quality seeds have been significant challenges facing Tanzania’s agricultural sector, especially for open-pollinated crops such as common beans, sorghum, and groundnuts. Marketplace traders purchase grains for sale from farmers who often rely on traditional varieties, which may have lost their effectiveness in combating emerging challenges such as pests, diseases, climate change, and variability. Despite the availability of improved climate-resilient varieties, limited promotional efforts have been made to increase their adoption among marketplace traders, who are mainly women. Moreover, the current promotion and awareness-creation efforts by public and private partners often target smallholder farmers, with limited success in increasing adoption and replacing old varieties. This study explored the preferred approaches by marketplace traders for receiving information about newly released climate-resilient varieties to enable them to switch to selling grains of new climate-resilient varieties. Quantitative data were collected from 657 marketplace traders (372 women and 285 men), and qualitative data were collected from 180 marketplace traders across rural and urban markets, with women comprising 58% of them. Content and ethnographic methods were employed to analyze the qualitative data, while descriptive analysis and a multivariate probit model (MVP) were used to analyze the quantitative data. The findings show that marketplace traders have limited information about the existence of the new climate-resilient varieties but are motivated to receive information about the new climate-resilient varieties due to the associated supply, quality, and yield advantages. Local radio stations, in-person meetings, posters placed in the local markets, and WhatsApp groups are preferred channels for sharing information about new climate-resilient varieties with marketplace traders and some farmers. Due to low smartphone ownership, female marketplace traders preferred phone calls, text messages, local radio, and in-person meetings to access various types of information. A single approach is not a one-size-fits-all solution; it may be effective in some contexts but not in others. Therefore, prioritizing a set of effective approaches that women prefer for sharing information about climate-resilient varieties would be more likely to achieve the intended adoption impacts.